Berbagai Metode dan Corak Penafsiran Al-Qur’an - Andi Malaka (LPPAIK Universitas Muhammadiyah Bandung, 2021)
Interpretation is very necessary because everyone expresses their thoughts by conveying a series of sentences which sometimes cannot be understood clearly without being followed by explanatory sentences. Interpretation of the Qur'an plays a role in helping humans grasp the secrets of Allah s.w.t and the universe, both visible and hidden. Proper interpretation is needed to understand the Qur'an properly and correctly, it requires proper interpretation so that to achieve this purpose, it is necessary to have a good mastery of the methodology of interpretation. The science of interpretation continues to grow and the number of books of interpretation continues to grow in various styles. The scholars of later commentary then sorted the books based on the method of writing into four forms of interpretation, namely: the Tahlili, ijmaii, Muqarin and Mawdhu'i methods. This paper describes some of these interpretation methods and explains the strengths and weaknesses of each method.